2017
DOI: 10.3126/jcmc.v6i3.16695
|View full text |Cite
|
Sign up to set email alerts
|

Contributing factors to relapse of drug addiction among clients attending rehabilitation centres of Dharan, Nepal

Abstract: Relapse is the resumption of substance after a period of abstinence. It is frustrating but frequent part of recovery process. Several substance including opiates, cocaine and alcohol have particularly has high relapse rate with majority of client relapsing within 1 year following treatment. The first 90 days after treatment are very vulnerable time. Hence, the objective of the study is to assess the contributing factors to relapse of drug addiction since the aftercare services, the psycho-social aspect of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 1 publication
4
14
0
Order By: Relevance
“…Peer pressure, social or family problems, craving, negative mood state and concentration difficulties were other factors commonly found to be contributing to relapse in both groups. Similar results were 9,15,16 observed in some previous studies .…”
Section: Resultssupporting
confidence: 92%
“…Peer pressure, social or family problems, craving, negative mood state and concentration difficulties were other factors commonly found to be contributing to relapse in both groups. Similar results were 9,15,16 observed in some previous studies .…”
Section: Resultssupporting
confidence: 92%
“…It was indicated that the social context can serve either as a resource or an obstacle for behavior change by the patient post treatment. For example, “negative peer influences have been noted in the development of substance use behavior and the promotion of relapse [ 9 , 33 ]. Similar authors found that patients were unable to resist either direct or indirect attempts by others to engage them in drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Substance use dependence are episodic, with periods of abstinence, reduction of use, and relapse the prevailing pattern, often with the course of events being influenced by external factors such as availability of drugs and societal pressures [ 9 , 15 ]. Moreover, various factors are associated with relapse to SUD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations